2018
DOI: 10.1039/c8nr07197g
|View full text |Cite
|
Sign up to set email alerts
|

Hydride-induced ligand dynamic and structural transformation of gold nanoclusters during a catalytic reaction

Abstract: This study provides molecular insights into the ligand dynamics and structural transformation of Au NC catalyst during 4-nitrophenol hydrogenation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 64 publications
0
20
0
Order By: Relevance
“…H − ions arising from BH 4 − has stronger affinity by the metal surface than most ligands, even those considered strong, like thiols. This replacement of adsorbates by hydride ions has also been proved for metal clusters of very small size ,. Hence, in presence of NaBH 4 , ligands on the surface of metal NPs can be re‐organized or even completely desorbed, conducting to a change in the expected catalytic activity.…”
Section: Resultsmentioning
confidence: 80%
“…H − ions arising from BH 4 − has stronger affinity by the metal surface than most ligands, even those considered strong, like thiols. This replacement of adsorbates by hydride ions has also been proved for metal clusters of very small size ,. Hence, in presence of NaBH 4 , ligands on the surface of metal NPs can be re‐organized or even completely desorbed, conducting to a change in the expected catalytic activity.…”
Section: Resultsmentioning
confidence: 80%
“…7,8,142,170 In addition, the increasingly known dynamics of metal atoms and/or SR ligands in each NC imposes additional difficulties to precisely control the alloying/ligandexchange sites in metal NCs. 163,[255][256][257] It should be noted that similar metal and ligand dynamics have also been demonstrated at the inter-cluster level, 59,249,250 which suggests that the stability and integrity of noble metal NCs in practical applications should be carefully evaluated in the corresponding surroundings.…”
Section: Discussionmentioning
confidence: 84%
“…The aforementioned partial decomposition mechanism well corroborates the hydride-assisted Au(I)-SR motif desorption-readsorption mechanism for the hydrogenation of 4-nitrophenenol. 250 19 ) by re-adsorbing SR or SR-[Au(I)-SR] x in the nal stage of the catalytic reaction, constituting a desorption-readsorption mechanism for the selective hydrogenation reaction of 4-nitrophenol. In another contribution, the authors also found that the hydrogenation pathway of 4-nitrophenol could be tunable based on the hierarchical structure of [Au 25 (p-MBA) 18 ] À .…”
Section: Molecular Interactions/reactions In Catalytic Application Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Murray and co-workers studied Au25 NCs with ligand-exchanged mixed monolayers (thiophenolate, hexanethiolate, or biotinylated ligands) using ESI-MS. 116,117 Mass spectrometry was again powerful for characterizing ligand exchange reactions in protected nanoclusters with selenolates or Tellurolates. [118][119][120][121] Again, time dependent experiments have permitted to push forward the understanding of the formation of Please do not adjust margins Please do not adjust margins cluster size conversion or surface ligand modifications as a function of ligand exchange strategies, [122][123][124][125][126] reactive agents [127][128][129][130][131][132][133] or etching process. 134,135 Probing the charge state of the metal core (or kernel) of nanoclusters is also an exciting field of investigation.…”
Section: Materials Advances Accepted Manuscriptmentioning
confidence: 99%